On Methylene Blue and Its Zinc Thiocyanate Complex in Connection with A New Spectrophotometric Determination of Zinc - Isjrin Noerdin (Journal of Mathematical and Fundamental Sciences, 1964)
Abstract. By reacting zinc with methylene blue and thiocyanate and measuring the decrease in absorbance, calibration curve for a photometric determination of zinc are found, which under suitable conditions are independent of the pH, the ionic strength, the temperature, and also of small differences. Ichtisar. Djika seng direaksikan dengan biru metilena dan tiosianat dan diukur berkurangnja absorpsi, akan terdapat garis kalibrasi untuk suatu penentuan fotometris baru untuk seng, jang, djika dipenuhi sjarat2 tertentu, tidak terpengaruhi oleh pH, "ionic strength", temperature dan djuga tidak oleh selisih waktu jang tidak terlampau besar.